Socio-cultural beliefs about an ideal body size and implications for risk of excess weight gain after immigration: a study of Australian residents of sub-Saharan African ancestry. Issue 8 (17th November 2021) - Addo, Isaac Yeboah; Brener, Loren; Asante, Augustine Danso; de Wit, John
ABSTRACT: Objectives: Though several studies have focused on risk factors associated with excess weight gain, little is known about the extent to which socio-cultural beliefs about body sizes may contribute to risk of excess weight gain, especially in non-Western migrant communities. Drawing on socio-cultural and attribution theories, this study mainly explored socio-cultural beliefs about an ideal body size among Australian residents who were born in sub-Saharan Africa (SSA). Implications of body size beliefs for risk of excess weight gain after immigration have also been discussed. Design: Employing a qualitative design, 24 in-depth interviews were conducted with Australian residents who were born in SSA. Thematic content analysis was undertaken to ensure that participants' experiences and views were clearly captured. Results: According to the participants, a moderately large body size is idealised in the SSA community and post-migration weight gain is commonly regarded as evidence of well-being. While desirability of a moderately large body size was noted by some participants, others were concerned about health risks (e.g. high blood pressure) associated with excess weight gain. Moreover, body size ideals seemed to be different for men and women in the SSA community and these ideals were mainly promoted by family and friends. Participants reported that women with very slim (skinny) body sizes are often regarded as persons suffering from health problems, whereas those with 'plumpy' body types are often considered beautiful. Participants also noted that men are expected to look well-built and muscular while those with big bellies are often seen as financially rich. Conclusions: Participants' interpretation of post-migration weight gain as evidence of well-being calls for urgent intervention as risk of excess weight gain appear to be high in this immigrant group.